Governing New York State - Pecorella, Robert F., 1948-; Stonecash, Jeffrey M. (State University of New York Press, 2006)
Because of its great diversity, New York State has more extensive social and political conflict than most states. In this indispensable guide to New York State politics, political institutions, and public policy, experts analyze how these conflicts are organized and represented, and how the political process and political institutions work to seek to resolve them. This newly updated edition of the classic text contains significantly revised material and many new contributors.